Peran Aqidah Dalam Mencegah Cyberbullying Dimedia Sosial (Studi Analisis Terhadap Instagram Mahasiswa Prodi Aqidah Dan Filsafat Islam) - Ananda Prathiwi (Medan Resource Center, 2021)
This study aims to examine and understand from the point of view and analyze the Instagram students of the Aqidah and Islamic Philosophy study program at the State Islamic University of North Sumatra regarding deviant actions that are currently rampant on social media, namely cyberbullying. This action is motivated by the existence of moral decadence. or a decrease in moral values that occurs in some people and impacts when using social media, especially on platforms. Instagram.Where from the results of the research that the author did, Instagram is the platform that is most often used today. The method used in this study is a qualitative method by describing facts in the field, as obtained from observations... documentation and interviews (interviews). From the data obtained, it is then analyzed using descriptive analysis which includes: data collection, data filtering, data classification and drawing conclusions. Therefore, the need for the role of aqidah in preventing the recurrence of this action by reinforcing aqidah in a way, namely first, by getting to know Allah SWT more closely, secondly worshiping Him, and thirdly studying Islamic teachings more deeply and then implementing them in daily life.